2021
DOI: 10.1007/s00238-021-01827-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on plastic surgery activities and residency programs in a tertiary referral centre in Iran

Abstract: Background On March 11, 2020, the World Health Organization (WHO) announced the COVID-19 outbreak as a new pandemic. In the meantime, plastic surgeons postponed their appointments due to the fair and rational allocation of medical supplies. These limitations made all junior and senior residents perform operations only on traumatic patients rather than those needing reconstructive procedures. This study aims to determine the effects of the COVID-19 pandemic on plastic surgery training programs in Iran. Also, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
3
0
1
Order By: Relevance
“…From March to August 2020, there was an average reduction of 14% in surgical interventions at Yaoundé Central Hospital compared to the same period the previous year. This result is lower than that found in a study conducted in Iran in 2021( 10 ), which reported a 23.5% decrease in the total number of surgeries during the pandemic. Our results are similarly lower than those found in a study conducted in Germany in 2020 by Haffer et al ( 11 ), which noted a 49.4% decrease in the total number of trauma and orthopaedic surgeries during the pandemic.…”
Section: Discussioncontrasting
confidence: 75%
“…From March to August 2020, there was an average reduction of 14% in surgical interventions at Yaoundé Central Hospital compared to the same period the previous year. This result is lower than that found in a study conducted in Iran in 2021( 10 ), which reported a 23.5% decrease in the total number of surgeries during the pandemic. Our results are similarly lower than those found in a study conducted in Germany in 2020 by Haffer et al ( 11 ), which noted a 49.4% decrease in the total number of trauma and orthopaedic surgeries during the pandemic.…”
Section: Discussioncontrasting
confidence: 75%
“…The pandemic’s long-term effect on the practises of plastic surgery, however, is still unknown, which necessitates more research in this regard. The significant reduction in craniofacial surgeries observed in this study also agrees with an investigation done by Kalantar et al [ 29 ]. The investigators attributed this decrease in the riskiness of the surgical site because the pharynx and upper digestive tract are where sick people often have the highest virus loads [ 30 ].…”
Section: Resultssupporting
confidence: 93%
“…A significant reduction in the rate of craniofacial surgeries was also observed in this study. This finding is consistent with that of a similar study that reported a 52% reduction in craniofacial surgeries [ 12 ]. This might be attributed to the riskiness of the operative area, as infected individuals tend to have the highest viral load in the pharynx and upper aerodigestive tract [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…The reduction was particularly remarkable during the lockdown period from March 25 to June 21, 2020, with a reduction rate of 94.44%. This finding is consistent with other similar studies conducted in Iran and southern India, where a significant decline in the number of plastic surgeries conducted after the pandemic was reported [ 8 , 12 ]. The reduction in the admission rate is thought to be partly due to the hospital's policy of prioritizing urgent and emergent cases and partly because of patients' fear of contracting COVID-19 infection in the hospital.…”
Section: Discussionsupporting
confidence: 93%